2021
DOI: 10.1002/brb3.2043
|View full text |Cite
|
Sign up to set email alerts
|

Hungarian validation of the Buss–Perry Aggression Questionnaire—Is the short form more adequate?

Abstract: Objective We aim to provide a publicly available Hungarian version of the BPAQ; compare the BPAQ factors to other personality traits; and compare both the original BPAQ factor structure provided by Buss and Perry (J. Pers. Soc. Psychol., 63, 1992, 452), the revised BPAQ‐SF factor structure by Bryant and Smith (J. Res. Pers., 35, 2001, 138), and the BAQ by Webster et al. (Aggress. Behav., 40, 2014, 120). Methods The validation of the Hungarian version of the BPAQ was carried out on a Hungarian university sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…We calculate a sum score with values ranging 0-24, with higher values indicating a more pronounced inclination to aggression. The instrument has been applied in a wide variety of cultures (Diamond and Magaletta, 2006;Vitoratou et al, 2009;Abd-El-Fattah, 2013;Zimonyi et al, 2021), including Germany (von Collani and Werner, 2005). Webster et al (2015) found high test-retest reliability among the four subscales indicating it measures a stable trait.…”
Section: Aggressionmentioning
confidence: 99%
“…We calculate a sum score with values ranging 0-24, with higher values indicating a more pronounced inclination to aggression. The instrument has been applied in a wide variety of cultures (Diamond and Magaletta, 2006;Vitoratou et al, 2009;Abd-El-Fattah, 2013;Zimonyi et al, 2021), including Germany (von Collani and Werner, 2005). Webster et al (2015) found high test-retest reliability among the four subscales indicating it measures a stable trait.…”
Section: Aggressionmentioning
confidence: 99%
“…The results suggest that the total and subscale scores of BPAQ had an adequate reliability in terms of internal consistency, and provide a valid measurement of physical aggression, verbal aggression, anger and hostility in the sample. A number of researchers have investigated the reliability and validity of this instrument, and the findings generally point in the direction of good psychometric properties with the qualification that the elimination of a few items improves the instrument; Harris et al ( 46 ) removed two items from the hostility subscale, Gerevich et al ( 35 ) removed two reversed scored items, Zimonyi et al ( 47 ) removed item 21 and item 27, while Nakano ( 48 ) removed three items. To develop a more appropriate measurement model, the present study identified a 27-item, four-factor measurement model with acceptable goodness-of-fit and high internal consistency, despite the removal of two items (item 9 from anger subscale and item 4 from the verbal aggression subscale).…”
Section: Discussionmentioning
confidence: 99%
“…The PTQ has been previously validated in languages other than English, including French [ 75 ], Spanish [ 76 ], Peruvian [ 69 ], and Polish [ 77 ]. Similarly, different versions of the Buss–Perry Aggression Questionnaire-Short Form (BPAQ-SF) exist, including Portuguese [ 78 ], Hungarian [ 79 ], Turkish [ 80 ], Chinese [ 81 ], Spanish [ 82 ], and Thai [ 83 ]. However, to the best of our knowledge, no research instruments are yet available in Arabic to assess aggression and repetitive negative thinking.…”
Section: Introductionmentioning
confidence: 99%